Applying music in exercise and sport - Karageorghis, Costas I. 1969- (Champaign, IL Human Kinetics, 2017)
This book combines contemporary research, evidence-based practice, and specific recommendations to enhance motivation and performance through music-related intervention. Readers will examine the psychological and physiological effects of music and learn how to apply scientific principles to personal workouts, group exercise classes, and a variety of sports.
Part 1. How music can help exercisers and athletes. Music in exercise and sport -- The science behind the music-performance connection -- Assessing music and measuring its effects -- Part 2. Using music to enhance exercise and workouts. Individual exercise and workouts -- Group exercise and workouts -- Exercise case studies and playlists -- Part 3. Using music to enhance sport training and performance. Individual sport training and performance -- Team sport training and performance -- Sport case studies and playlists.
Includes bibliographical references and index.
Keywords: Music and sports; Music -- Psychological aspects; Exercise -- Psychological aspects; Sports -- Psychological aspects; Exercise music -- Discography